Environmental science / Karen Arms - Arms, Karen (USA: Saunders College Publishing, 1994)
Part 1 overview, science and environment chapter, how humans affect their environment; part 2 some basic ecology, energy, chemistry, and climate, biodiversity and habitats, ecosystems and how they change; part 3 populations, natural populations, human populations, population, environment, and disease; part 4 natural resources, fossil fuels and nuclear energy, energy conservation and renewable energy, fresh water, the oceans, nonfuel mineral resources agricultural land, food and hunger, species and extinction chapter, wilderness and forest; part 5 pollution, toxic and solid waste, pollution and water, air pollution and noise
Índice, ilustrado mapas, tablas, gráficos
Col. Agro
Keywords: 1. ECOLOGÍA 2. ARMS ENVIRONMENTAL 3. AGROFORESTAL